HEALTH COMMUNICATION STRATEGIES AND TREATMENT CONTINUITY AMONG “TEST AND START” ANTIRETROVIRAL THERAPY CLIENTS IN ZOMBA, MALAWI: health communication strategies, antiretroviral therapy, ART adherence, test and start, Zomba, Malawi (Proceedings of the International Conference on Public Health, 2023)
Malawi adopted test-and-start, a strategy for initiating clients to antiretroviral therapy (ART) within 7 days of being diagnosed HIV positive regardless of CD4 count, in 2016. Despite notable improvements in ART coverage, adherence remains suboptimal. A cross-sectional convergent parallel mixed methods study was conducted between May and August 2022   to assess health communication strategies associated with ART continuity among test-and-start clients in Zomba District, southern Malawi. Random sampling was used to select 8 health facilities   and   325 test-and-start clients   from clinic registers to collect quantitative data. Key variables were client knowledge of test-and-start, media of accessing information about test-and-start and HIV status disclosure.  Qualitative data were collected amongst 68 health workers and expert clients, positive deviants in ART adherence and mentors of fellow clients.  Eight focus group discussions and eight key informant interviews were conducted. Logistic regression and thematic analysis were used to analyze quantitative and qualitative data respectively. Trans theoretical Model (TTM) was used to conceptualize results. Results showed that only Follow-up calls by health worker was significantly associated with adherence (OR=1.787, 95% CI: 1.41-2.51).   Client knowledge, status disclosure and quality of counselling did not influence ART adherence. Qualitative results showed that intrapersonal level   strategies such as prior knowledge about test-and-start influenced adherence while   one’s perceived health status and negative attitude towards test-and-start potentially influenced non-adherence. Interpersonal level strategies such as disclosure, perceived quality counselling had potential to influence adherence. For effective adherence, health communication strategies should target at empowering ART clients’ agency to adopt a healthy behaviour at various stages of health behaviour change process. Appropriate determination of ART clients’ stages in the behaviour change process is critical if health communication strategies are to be used effectively in promoting treatment continuity.
Keywords: health communication strategies; antiretroviral therapy; ART adherence; test and start; Zomba; Malawi